Public pension, capital stock and consumption in rural China - Yang, Zaigui; Cao, Yuan (Advances in Social Sciences Research Journal, 2015)
This paper investigates the rural public pension in China by employing an overlapping-generations model. We examine the effects of the individual contribution rate, village subsidy rate, local government allowance rate, basic pension benefit rate and population growth rate on the capital-labor ratio, per capita consumption and pension benefits. Raising the individual contribution rate only increases the per capita pension benefits, and has no effect on the capital-labor ratio and per capita consumption. Raising both the village subsidy rate and local government allowance rate increases the capital-labor ratio, per capita consumption and pension benefits. Raising the basic benefit rate decreases the capital-labor ratio and per capita consumption, while increases the pension benefits. A rise in the population growth rate decreases the capital-labor ratio, per capita consumption, and pension benefits. In accordance with the effects and their intensities, it will do more good than harm to raise the individual contribution rate and village subsidy rate, maintain the present basic benefit rate and accordingly raise the local government allowance rate by adjusting the structure of fiscal expenditures, and control the population growth rate.